2020
DOI: 10.21203/rs.3.rs-77460/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide Study of SBT Genes in Eight Plant Species: Evolution and Expression Outlines for Development and Stress

Abstract: Background: Subtilisin-like proteases (or subtilases, SBT), a specific family of serine peptidases, are a very big family in plants. Previous studies showed association of SBTs with environment response and development. However, it is still unclear about the function and features of SBTs. Also, there is little information about SBTs classification or protein function research.Results: The characters of SBTs in eight plant species including Arabidopsis, rice, wheat etc. were analyzed. The analysis mainly contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Studies of gene repetition events illustrate the potential spread mechanism of TaSBT, suggesting that duplicate gene pairs tend to come from the same subfamily (Figure 2). Gene structure and motif composition further demonstrated the relative conservatism among members of the same subfamily (Figure 3), and these results were consistent with previous studies [21].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Studies of gene repetition events illustrate the potential spread mechanism of TaSBT, suggesting that duplicate gene pairs tend to come from the same subfamily (Figure 2). Gene structure and motif composition further demonstrated the relative conservatism among members of the same subfamily (Figure 3), and these results were consistent with previous studies [21].…”
Section: Discussionsupporting
confidence: 91%
“…In total, 218 TaSBTs possess a peptidase inhibitor I9 domain that plays a role in enzyme activation. Subcellular localization prediction analysis showed that TaSBTs were localized in chloroplasts (104), cell wall (58), vacuolar membrane (52), plasma membrane (21), endoplasmic reticulum (17), cytoplasm (15), and nucleus (8), with the largest number of loci in chloroplasts (Table S1).…”
Section: Genome-wide Identification Of Wheat Sbt Protein Familymentioning
confidence: 99%
See 2 more Smart Citations
“…The Hidden Markov Model (HMM) (Potter et al, 2018) for the Peptidase_S8 domain (PF00082) (Wen et al, 2020) was acquired from the Pfam database (Bateman, 2004) and utilized as a query to interrogate the soybean genome database retrieved from Ensembl Plants (Bolser et al, 2015). Concurrently, SBT protein sequences from Arabidopsis thaliana were sourced from the Arabidopsis Information Resource (TAIR) database (Lamesch et al, 2012) and subjected to BLASTP comparisons against the soybean protein database.…”
Section: Identifcation and Characterization Of Sbt Genes In Soybeanmentioning
confidence: 99%